Rational Emotive Behavior Theraphy Approach to Overcoming Traumatized Child Victims of Domestic Violence - Afni Rizkah Pulungan (Indonesian Institute for Counseling, Education and Theraphy, 2020)
Trauma is a psychological symptom that causes a child to be frightened due to an event he has experienced that causes a child to imagine an event that makes him afraid or traumatized, so there is need for help to overcome it. Rational Emotive Behavior Theraphy (REBT) is an approach that rationalizes irrational children's thinking to be rational. This article belongs to the type of qualitative research with a case study approach. The subject in this article is one student with criteria as a child who experiences domestic violence by his biological father who is separated from his mother. Taking the subject of this study using purposive sampling method. This study uses REBT approach techniques, data collection by interview counseling and observation. The technique guarantees the validity of the data carried out by building close relationships with subjects and informants naturally and continually making observations. Data analysis techniques were carried out by means of data reduction, data display and conclusion drawing and verification.